Fabrication and Performance Evaluation of an Engine-Operated Weeding Machine for Wheat plantation (American Journal of IR 4.0 and Beyond, 2023)
Wheat crops are severely hampered by weeds, which also significantly reduce productivity. Manual weeding requires a lot of time and effort. Chemical weed management is harmful to both the environment and people. Today’s agriculture sector needs non-chemical weed management to meet consumer demand for premium food items and pay close attention to food safety. The objectives of the study was to evaluate the performance of an-engine operated weeder by evaluating the weeding efficiency, plant damage, effective field capacity, field efficiency, fuel consumption, performance index, energy consumption, and cost economics of engine operated weeder in wheat crop. The experimental design was a randomized complete block design and evaluation was conducted at three weeder forward speeds (1.5, 2, and 2.5 km/hr), two depths of operation (from 0 to 20 and from 0 to 40 mm), and three levels of soil moisture content (9.4, 12.34 and 15.25%). The performance of the weeder was found to be optimum at 15.25 percent soil moisture content with 0 to 40 mm depth of operation at a forward speed of 1.5 km/hr. The results revealed that maximum weeding efficiency of 90.1 percent was obtained with lower plant damage of 3.31 percent whereas the effective field capacity, field efficiency, fuel consumption, performance index, and energy consumption were found to be 0.052 ha/hr, 85.99%, 0.41 l/hr, 276.78 ha/hp, and 481.71 MJ/ha, respectively. The analysis revealed that forward speed, depth of operation, and soil moisture had significant effects on weeding efficiency, plant damage, effective field capacity, and fuel consumption at P